"Adaptation of Operational Management to Hybrid and Remote Work Trends" - Mohammad Ali (Journal of Economics, Management, Accounting, Business, Educational, Technology, and Social Science, 2025)
Technological developments and changes in global work patterns have encouraged many organizations to adopt hybrid and remote work models. Operational management adaptation is the main key in ensuring effectiveness, efficiency and productivity in this situation. This article discusses how organizations adapt their operational processes, from human resource management, communication systems, performance monitoring, to the use of digital technology. With a strategic and flexible approach, companies can optimize collaboration, maintain organizational culture, and meet business targets amidst the dynamics of remote work. This study also identifies the main challenges and best practices that can be used as a reference in building adaptive operational management in the era of hybrid and remote work.